2016
DOI: 10.1002/app.44114
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative relation between the relaxation time and the strain rate for polymeric solids under quasi‐static conditions

Abstract: Relaxation time is an essential physical quantity reflecting the hysteresis of the microstructure of materials. To associate the relaxation time with the strain rate, the stress-strain curves of six types of polymers at low strain rate were normalized, and a nondimensional generalized Maxwell model incorporating strain-rate-dependent relaxation times was obtained by the internal variable theory of irreversible thermodynamics. The results indicate that the constitutive equation may capture well the normalized s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The correlation coefficient close to 1 indicated that the constitutive model was accurate for calculating the mechanical behavior of EPI films in humid surroundings. As elaborated in the published works [27,28,29,30], relaxation time is an intrinsic property describing the hysteresis of chain segments of polymer or its composites under external stress. In order to investigate the moisture influence on the mechanical behaviors of EPI film in greater depth, we attempted to determine the relaxation time of a cured sample at 0–80% RH as follows.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation coefficient close to 1 indicated that the constitutive model was accurate for calculating the mechanical behavior of EPI films in humid surroundings. As elaborated in the published works [27,28,29,30], relaxation time is an intrinsic property describing the hysteresis of chain segments of polymer or its composites under external stress. In order to investigate the moisture influence on the mechanical behaviors of EPI film in greater depth, we attempted to determine the relaxation time of a cured sample at 0–80% RH as follows.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, under low frequency loadings, the relationship between relaxation time of the material and loading frequency could also be fitted by a power function. That is, regardless of the value of loading frequency, the relationship between relaxation time and loading frequency could be described by a power function, which was similar to the power relationship between relaxation time and strain rate (Chen et al, 2016) [11].…”
Section: Mechanical Performance Analyses and Discussionmentioning
confidence: 95%
“…To address this problem, some researchers have proposed rate-dependent models for relaxation time under large-deformation and long-term loading [9][10][11]. For instance, Chen et al [12,13] investigated the responses of various polymeric materials under quasi-static compression and found a power relationship between relaxation time and strain rate. For polymer materials under cyclic loading, the evolution of their material parameters was also studied.…”
Section: Introductionmentioning
confidence: 99%